The Financial Crisis as an Overshooting Phenomenon - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2009)
Inspired by Dornbusch's model of exchange rate overshooting we develop a theory of stock market behaviour. The idea is that stock market prices overshoot and undershoot their long-run equilibrium values which are determined by the development in the real economy. The overshooting is fuelled primarily by a loose monetary policy. The simple macro model consists of three markets - the money market, the stock market and the goods market - interacting with different speeds of adjustment. The goods market slowly adjusts relative to the money and the asset market. This model can explain some of the major features of the global financial crisis, having its origin in the loose monetary policy in the USA and spreading its recession-plagued effects all over to the world economy. The model focuses primarily on the monetary interpretation of the present crisis leaving aside the complex interactions of the real estate bubble in the USA, followed by the innovation of new financial instruments which were sold all over the world, hoping to disperse the inherent risks. Nor does this model deal with the institutional aspects of the financial crisis (the failed behaviour of banks, the banking crises, unregulated financial markets, etc.). These are questions of better international regulation of the financial industry touched upon by the G-20 summit in London.
Keywords: 330; Financial Crisis; Open Economy Macroeconomics; Stock Markets; Business Cycles; Finanzkrise; Internationaler Finanzmarkt; Spillover-Effekt; Konjunktur; Geldpolitik; Wirkungsanalyse; Offene Volkswirtschaft; Theorie